Induction of Endothelial Cell/Macrophage Procoagulant Activity: Synergistic Stimulation by Gamma Interferon and Granulocyte-Macrophage Colony Stimulating Factor - Zuckerman, Steven H; Surprenant, Yvonne M (Thrombosis and Haemostasis, 1989)
Inflammatory mediators such as endotoxin can stimulate the expression of procoagulant activity on both endothelial cells and macrophages while the monokines Interleukin 1, IL-1, and Tumor Necrosis Factor, TNF induce procoagulant activity on endothelial cells. Incubation of murine peritoneal macrophages with suboptimal concentrations of endotoxin results in a two fold increase in procoagulant activity. Macrophages incubated with gamma interferon, IFN γ, or Granulocyte-Macrophage Colony Stimulating Factor, GM-CSF, for 16 hours prior to endotoxin stimulation demonstrated a synergistic increase in procoagulant activity. A synergistic increase in procoagulant activity was also observed with primary cultures of human umbilical cord endothelial cells incubated with recombinant human IFN γ for 16 hours prior to endotoxin, TNF, or IL-1 stimulation. Human GM-CSF had no stimulatory effect on endotoxin or monokine induced endothelial cell procoagulant activity. The augmentation of macrophage and endothelial cell procoagulant activity by IFN γ and GM-CSF may provide a novel explanation for the role of these cytokines in acute and chronic inflammation.
Keywords: IL-1; TNF; Endotoxin; Inflammation; Tissue factor